Blindness Management for Retinitis Pigmentosa with Cataract senile immature : A Case Report: Poster Presentation - Case Report - General practitioner - Fitria Nuraisa; Anggraeni Sp. M , M.Kes, dr Nila; Rahman Sp.M, dr Faisal (Majalah Oftalmologi Indonesia, 2023)
Introduction : Retinitis Pigmentosa (RP), also called pigmentary retinal dystrophy, is the term of hereditary retinal diseases that feature degeneration of rod and cone photoreceptors. The most common complication of RP is cataract. Cataract formation is most likely the result of retinitis pigmentosa-related inflammation response. Cataract is an important secondary cause of visual impairment in RP. Case Illustration : A 39-year old female came to the Hospital with complaint of having blurred vision in both eyes since four years ago. Ophthalmologic examination revealed that visual acuity for her right and left eye was 1/300. Anterior segment examination was revealed lens opacification in right and left eye. Funduscopy examination was revealed bone spicula in right and left eye. Patient was diagnosed with retinitis pigmentosa with cataract senile immature in both eyes. Phacoemulsification with intraocular lens (IOL) implantation were done as surgical management for the right eye. Discussion : RP is one of the leading causes of irreversible blindness. The possible explanation of reduced vision in RP can be photoreceptor cell death and treatable complications of RP. Cataract is the most common anterior segment complication described in RP. Visual acuity in RP could be improved for the complications that receive effective treatment, especially with the improvement of the cataract surgery. However, the visual prognosis and surgical risk following cataract surgery is uncertain, the cataract surgery should still be considered in patients with RP. Phacoemulsification with IOL implantation remains the most preferred method to manage cataracts. Conclusion : Cataract surgery in patients with RP leads to significant improvements in visual acuity